Diferenças na autorregulação entre meninos e meninas em creche - Mérilin Kenne Mezera (2023)
The present study aims to examine gender differences in the outcomes of self-regulation assessment of children in daycare, using direct measures of executive functions and the educators' report questionnaire, from a multimethod approach. The sample was collected as part of the Quality Matters project2 (2017-2019). A total of 258 Portuguese children (134 boys and 124 girls), with a mean age of 35 months for both genders (girls M = 35,08, SD = 3,73, boys M = 35,26, SD = 4,22) and 29 lead teachers from each classroom participated in this study. To assess children's self-regulation measures of attention, working memory and inhibitory control were used are they: the visual attention subtest from the Developmental Neuropsychological Assessment (NEPSY; Korkman et al., 1998), the hidden toy task (Mulder et al., 2014) and the toy wrap task from the Preschool Self-Regulation Assessment (PSRA; Smith-Donald et al., 2007), respectively. Referring to teacher-reported self-regulation, the Classroom Behavioural Self-Regulation subscale of the Child Behaviour Rating Scale (CBRS; Bronson et al., 1990) was used. Girls showed higher levels than boys on tests of attention and inhibitory control, but not working memory. The teachers' assessment also pointed to better performance by girls. In summary, gender differences in self-regulation and executive functions are detectable at early ages. Key words: self-regulation, executive function, gender, toddlers.